GC-MS Analysis, Oral Toxicity Evaluation, and Molecular Docking Studies of Ocimum tenuiflorum L. Essential Oil: Exploring its Anti-Diabetic Potential through Peroxisome Proliferator-Activated Receptor-Delta (PPARδ) Activation - Tamang, Ashika; Parajuli, Nirmal; Poudel, Manila; M.C., Shiva; Shrestha, Aakar; Shrestha, Timila; Bharati, Samjhana; Maharjan, Binita; Bhattarai, Deval Prasad; Marasini, Bishnu P.; Subin, Jhashanath Adhikari; Shrestha, Ram Lal Swagat (Amrit Research Journal, 2024)
Ocimum tenuiflorum (O. tenuiflorum), commonly known as Tulsi, is an aromatic herb with significant medicinal properties, particularly in the management of diabetes. This study aimed to extract essential oil from the leaves of O. tenuiflorum, perform a comprehensive GC-MS analysis, evaluate acute oral toxicity, and assess its anti-diabetic potential through computational molecular docking with the peroxisome proliferator-activated receptor-delta (PPARδ) protein. The essential oil was extracted using hydro-distillation, and GC-MS identified 28 compounds, with (E)-caryophyllene, β-elemene, and trans-isoeugenol being the most abundant. Molecular docking against PPARδ (PDB ID: 5U3R) highlighted rimuene, himachalane, valencene, and nootkatene as top candidates, exhibiting strong binding affinities comparable to the reference drug seladelpar. Predominantly hydrophobic interactions were observed due to the volatile, non-polar nature of the compounds in the oil. Acute oral toxicity tests showed an LD50 >2000 mg/kg body weight which confirmed the safety of the essential oil, with low toxicity profile. This study identifies rimuene and himachalane as promising PPARδ modulators, suggesting further in vitro, in vivo, and computational evaluations to validate their therapeutic potential in diabetes management.